Diabetes mellitus and Ramadan. A narrative review of literature (Italian Journal of Public Health, 2011)
Background: The medical ramification of fasting among patients with diabetes is largely unknown; thepurpose of the review is to find out how diabetes mellitus is managed during the month of Ramadan.Methods: Literature published on diabetes management during the month of Ramadan in the Middle-Eastare aimed at getting a global picture of this condition at a time when diabetes is having an adverse effect onhealth care delivery. I hope the review will be a useful and comprehensive source on the subject (diabetesmellitus) for researchers, academics and clinicians who care for the increasing number of diabetic patientsand help health care providers curb the tide of the diabetes epidemic. The search includes available articlespublished, by using the keywords “Diabetes Mellitus”, “Ramadan” and “fasting” covering epidemiology,clinical, management and complication profile.Results: Studies have shown that fasting among diabetic patients carries the potential risk of dangeroushypoglycaemia and hyperglycaemia, diabetic ketoacidosis and thrombosis. The EPIDIAR study was thelargest study where 50% of the whole sample changed their treatment and hypoglycemia was the onlyobserved event. There are also few studies which evaluated specific management modalities.Conclusion: It follows from this review that Ramadan fasting is acceptable for well balanced diabeticpatients, conscious of their disease and compliant with their diet and drug intake. Patients willing to fastmust be advised to undertake control of their glycaemia several times a day to prevent hypoglycemia risksduring daytime fasting or hyperglycemia during the night.
Keywords: diabetes mellitus; Ramadan; fasting